Crystallinity and wettability induced osteogenic behaviors of commercially pure Ti and Ti-6Al-4V alloy implant surfaces having multiscale surface topography. (2021) - Abhijith, N.V.; Priyanka, C.P.; Sudeep, U.; Ramachandran, K.K.
Abstract: The influence of multiscale topography imparted through laser texturing of titanium based bioimplant surfaces on osteogenic behaviours is investigated. The synergistic effects of surface topography, surface physical and chemical behaviours appears to have improved the initial cell adhesion and proliferation. Micro grooves having embedded nano ripples as periodic surface structures were micro-fabricated on two different grades of specimens; commercially pure titanium and Ti-6Al-4V titanium alloy. The surface characteristics, chemical composition and phase constitution of the micro-fabricated surfaces were investigated by confocal microscopy, XPS and XRD analysis. The hydrophilicity of the samples was assessed by measuring the water contact angles and the results have been correlated with the surface chemistry. The response of osteoblasts cells seeded on the laser textured surfaces in standard controlled conditions was investigated using fluorescence microscopy and SEM. The results showed that the presence of multiscale topography enhances cell adhesion and provide a definite orientation for osteoblast cells to grow along the direction of the micro grooves. Surface oxidation states of titanium along with the presence of crystalline phase and improved hydrophilicity appeared to have a major role in the preferential integration of bone tissues on the laser textured specimen surfaces.